Smuggling of Migrants in Malaysia: The Case Study of Illegal Immigrants in the Northern Region - Ajis, Mohd Na'eim; Ahmad Zakuan, Ummu Atiyah; Mohd. Zain, Zawiyah; Keling, Mohamad Faisol (College of International Studies, Tamkang University, 2019)
The article discusses about migrant smuggling activities in the Northern Region of Peninsular Malaysia. Issues discussed include countries and borders that involved in the smuggling of migrant, types of transportation used, charges paid to the syndicates, parties involved in the process and the tactics of human smuggling. The data sample of this study are taken from 54 illegal immigrants who are being detained at the Immigration Detention Centre at Sik, Kedah and also those who settled in several districts in the Northern part of the Peninsular Malaysia. Relevant authorities like Malaysian Maritime Enforcement Agency, Malaysia Immigration Department and Border Ranger Regiment, are being interviewed. Findings reveal that the activities of migrant smuggling are occurring in the Northern Region of the Peninsular Malaysia. The authorities are continuously improvised the monitoring methods to curtail the migrant smuggling however, the syndicates are often ahead of the authorities and getting difficult to be traced